Digital Marketing Analysis of Customer Satisfaction's Impact on Company Brand Image: Quantitative Study - Dendi Sujatmika; Rimayani Rimayani; Nunung Ayu Sofiati; Mochammad Mukti Ali; Yoyo Sudaryo; Riyandi Nur Sumawidjaya; Dadan Abdul Aziz Mubarok (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the influence of digital marketing on customer satisfaction and its impact on brand image, particularly among consumers of PT. YXY Motors. In today's digital era, the use of online media such as websites and applications has become a key strategy for companies to reach consumers. This study employs a quantitative approach using a survey method with 30 respondents, and a questionnaire as the measurement tool, which has been validated and tested for reliability. The results indicate that the implementation of digital marketing at PT. YXY Motors is quite good, with social engagement as the strongest aspect. However, there are still shortcomings, especially in terms of the duration of digital visits. Customer satisfaction is also considered to be in the fairly satisfied category, with expectations as the dominant aspect and perception as the lowest. Meanwhile, PT. YXY Motors's brand image is in the fairly good category, with the reputation dimension having the highest score and affinity as the lowest. Data analysis shows that digital marketing has a significant effect on customer satisfaction, and customer satisfaction has a positive impact on the company's brand image. These findings indicate the importance of optimal digital marketing management to increase consumer loyalty and positive perceptions of the Yamaha brand.